Histomorphology of Parotid Salivary Gland in Sheep (Ovis aries) - Muthukrishnan, S.; Basha, Sabiha H.; Ramesh, Geetha; Ushakumary, Ushakumary; Rajathi, S.; Kumaravel, A. (Indian Journal of Veterinary Anatomy, 2013)
Histomorphology of parotid salivary gland was conducted in different prenatal age groups. In all the age groups, the gland was surrounded by a connective tissue capsule that radiated to form septae which divided the glandular parenchyma into many lobes and lobules. The connective tissue had dense collagen, reticular and few elastic fibres alongwith large blood vessels and nerves. The parotid salivary gland was characterised by purely serous acini having 4 to 6 pyramidal cells with distinct lumen.